Cellular Griffiths-like phase - Squillante, Lucas [UNESP]; Mello, Isys F. [UNESP]; Ricco, Luciano S.; Minicucci, Marcos F. [UNESP]; Ukpong, Aniekan Magnus; Seridonio, Antonio C. [UNESP]; Lagos-Monaco, Roberto E. [UNESP]; de Souza, Mariano [UNESP] (Elsevier, 2024)
Protein compartmentalization in the frame of a liquid-liquid phase separation is a key mechanism to optimize spatiotemporal control of biological systems. Such a compartmentalization process reduces the intrinsic noise in protein concentration due to stochasticity in gene expression. Employing Flory-Huggins solution theory, Avramov/Casalini's model, and the Grüneisen parameter, we unprecedentedly propose a cellular Griffiths-like phase (CGLP), which can impact its functionality and self-organization. The here-proposed CGLP is key ranging from the understanding of primary organisms' evolution to the treatment of diseases. Our findings pave the way for an alternative Biophysics approach to investigate coacervation processes.
Keywords: Cell criticality; Flory-Huggins solution theory; Griffiths phase; Grüneisen parameter; Primary organisms; Protein compartmentalization